Relationship between herbivory of the green turtle Chelonia mydas (Testudines: Cheloniidae) with seagrass meadow structural complexity at Cahuita National Park, Limón, Costa Rica - Moya-Ramírez, Jairo (2025)
Introduction: Seagrasses are habitat for the green turtle (Chelonia mydas). At Cahuita National Park (CNP), seagrass have been monitored since 1999. Over time, the canopy complexity of the dominant seagrass species (Thalassia testudinum) has declined. However, seagrass spatial variability and the turtle's interactions with these meadows at Cahuita remain poorly studied. Objective: We aimed to assess the distribution and composition of seagrass meadows in CNP and quantify the intensity of C. mydas herbivory. Methods: Seagrass meadows characterization was done in 2019 and 2021. Sampling points were distributed systematically every 200 m. When seagrasses were present, points were sampled every 50 m for greater resolution. Water depth and seagrass cover by species were quantified at each point. In 2019, additional metrics included sediment carbon content, shoot density, photosynthetic biomass, and leaf area index. Sea turtle density was calculated using aerial video transects, and abundance estimated from density and reef lagoon area. Herbivory rates were estimated by seagrass tethering experiments and underwater videos in 2021. Results: Seagrass meadows were found at depths between 0.4–5.3 m. Mean sediment organic carbon was 2 % and increased slightly at higher seagrass biomass. Carbonate was 40 % and did not vary spatially. Seagrasses at CNP were dominated by T. testudinum, with minimal presence of Syringodium filiforme, Halodule wrightii, and Halophila decipiens. Between 2019-2021, seagrass cover declined by 52 %, from 54.7–24.7 ha in the area sampled both years. Sea turtle length ranged from 20-80 cm. Estimated density was 0.6 ± 0.6 turtles/ha and abundance was 36-211 turtles within the reef lagoon. Underwater videos showed that C. mydas is the main herbivore of T. testudinum in the meadow, with herbivory rates from 12–182 cm2/s. Conclusions: Chelonia mydas plays a significant role in shaping seagrass canopy complexity and distribution at CNP, highlighting the need for integrated ecological monitoring and conservation efforts, particularly under the challenges posed by climate change and anthropogenic pressures.